2022
DOI: 10.1016/j.prosdent.2020.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Peri-implant marginal bone changes with implant-supported metal-ceramic or monolithic zirconia single crowns: A retrospective clinical study of 1 to 5 years

Abstract: Metal-ceramic is considered as the standard material for implant-supported prostheses because of its adequate strength and acceptable esthetics. 1 More recently, zirconia has also been used for implant-supported prostheses, 2 with similar biologic complications and enhanced esthetics as metalceramic prostheses. 3,4 However, the high fracture rates of veneering porcelain have also been observed in zirconiaceramic prostheses. 5,6 Monolithic zirconia without veneering porcelain has been reported to be a more frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Nowadays, dental clinicians can benefit from a wide range of definitive prosthetic materials, both conventional and modern ones, for the fabrication of implant-supported fixed prostheses (metal–ceramic prosthesis—including ceramic-veneered titanium; metal–resin prosthesis; monolithic zirconia prosthesis; ceramic-veneered zirconia prosthesis; lithium disilicate prosthesis; hybrid ceramics prosthesis). The selection of these materials for a specific clinical case is correlated with the implant-supported prosthesis design, number of implants, implant location (upper or lower jaw), type of connection, aesthetic requirements, masticatory force, static and dynamic occlusal scheme, and chewing pattern [ 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. It is acknowledged that metal–ceramic fixed dental prostheses (cast metal infrastructure and veneering ceramic) exhibit a good long-term clinical survival rate, both in the anterior and posterior regions of dental arches [ 99 ].…”
Section: Definitive Prosthetic Materials Used For Obtaining Oral Impl...mentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, dental clinicians can benefit from a wide range of definitive prosthetic materials, both conventional and modern ones, for the fabrication of implant-supported fixed prostheses (metal–ceramic prosthesis—including ceramic-veneered titanium; metal–resin prosthesis; monolithic zirconia prosthesis; ceramic-veneered zirconia prosthesis; lithium disilicate prosthesis; hybrid ceramics prosthesis). The selection of these materials for a specific clinical case is correlated with the implant-supported prosthesis design, number of implants, implant location (upper or lower jaw), type of connection, aesthetic requirements, masticatory force, static and dynamic occlusal scheme, and chewing pattern [ 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. It is acknowledged that metal–ceramic fixed dental prostheses (cast metal infrastructure and veneering ceramic) exhibit a good long-term clinical survival rate, both in the anterior and posterior regions of dental arches [ 99 ].…”
Section: Definitive Prosthetic Materials Used For Obtaining Oral Impl...mentioning
confidence: 99%
“…Despite this, ceramic-veneered zirconia has been successfully used for implant-supported prostheses as it presents better esthetics than metal–ceramic prostheses, very good mechanical behavior, and excellent biocompatibility. Moreover, monolithic zirconia prostheses have been reported to be more fracture-resistant, the incidence of ceramic chipping being eliminated [ 102 ].…”
Section: Definitive Prosthetic Materials Used For Obtaining Oral Impl...mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that monolithic zirconia with no veneer possesses greater fracture resistance than traditional ZrO 2 , and it is anticipated that this will lead to a decrease in the frequency of porcelain fracture in the region of the posterior teeth [64]. Shen et al performed a retrospective clinical analysis on the monolithic ZrO 2 single crowns and tried to learn more about the performance of monolithic ZrO 2 prostheses that are held in place by implants [65]. They took panoramic radiographs at various times throughout the therapy and the follow-up visit to research the marginal bone level (MBL).…”
Section: Zro 2 In Dentistrymentioning
confidence: 99%
“…As reported, monolithic zirconia without veneer has better fracture resistance than traditional zirconia and is expected to reduce the incidence of porcelain fracture in the posterior tooth area (29). Shen et al performed a retrospective clinical study of 1-5 years which included 224 patients treated with 327 implants and restored with metal-ceramic or monolithic zirconia single crowns to evaluate the clinical properties of implant-supported monolithic zirconia prostheses (30). They studied the marginal bone level (MBL) by taking panoramic radiographs at different stages during the treatment and follow-up visit.…”
Section: Ai In Biomedical Applications Of Zirconia In Dental Devices the Application Of Zirconia In Dentistrymentioning
confidence: 99%